Envisioning a new accountability - Lehman, Cheryl R. (Emerald, 2007)
Sustainable environments, global networks, ethical financial reporting, and emancipatory accounting are increasingly shaping social and accounting dialogue. This volume contributes to a visionary accounting practice in its expansive coverage of issues and geographical perspectives prompting changes in social beliefs and levers of power.Examining these concerns with surveys and contributions from Australasia, North America, Europe, and Africa, the authors expose significant influences of the World Bank, the nature of global social investment funds, and how social responsibility is defined, perceived, and managed. Corporate and government accountability, enhancing the integrity of audited financial statements, and reforming balances of nature and power, are among the dialogue in this volume. Revealing the interconnectedness of accounting practice, corporate social responsibility, technology, the natural environment, spirituality and behavior, the authors provide new visions and potential for enhancing social policies and economic justice.
Keywords: Business & Economics -- Accounting -- Governmental.; Public finance accounting.; Accounting.; Finance.; elektronické knihy; electronic books